The Bullet and the Language were the means of Subjugation- Ngugi’s Approach to Study the Phenomena of Enslavement: A Close Study of the Decolonizing the Mind - Raj, M Bal (International Journal of English Literature and Social Sciences (IJELS), 2019)
The African literature abounds with the rich contextual theories of post colonialism conglomerated by the genres of poetry, fiction, drama and pure theoretical works which breathed their life give synergy through the continent’s experience of brutal colonization. The heart of darkness is not heartless. The darkness does not pervade the inner core of humanity of the Dark Continent, it is darkness of the West masters which made them to see it with their blind eyes - for a blind man everything seems dark. Ngugi Wa Thiongo hails from Kenya as a critic of post colonial literature and politics. His vivid narrative of protest against the maneuvers of suppressive nature of neo colonization where white masters are replaced by the black native masters who were just shadows of the colonizers devoid of any pride or sense of dignified identity. He triumphantly wielded ‘Gikuyu’ against alien linguistic domination to express the local aura of Africanism. He experienced the horrors of communal violence between Christians and non-Christians the despondency of which made him remove the surname James and prompted to become Ngugi Wa Thiongo. ‘Decolonizing the Mind: the Politics of Language in African Literature' which urges for ideological as well as linguistic decolonization is a milestone in African literature which focuses on the prospects of using native tongue instead of colonizer’s language to represent the essence of African living experience. Chinua Achebe and Ngugi stand apart from each other on the idea of language for initiating the process of decolonization. My paper would discuss the various aspects of language and ideological framework of the African colonialism which is present in ‘Decolonizing the Mind’, and the difference between post colonialism and the process of decolonization. I also strive to construe ‘Language the suitable’ for protest, for realization and for creation of self.